Interfacial and Interlaminar Shear Strength of Unidirectional Viscose Fibre-Reinforced Epoxy Composites—an Overview of the Comparability of Results Obtained by Different Test Methods - Graupner, Nina; Müssig, Jörg (Frontiers in Materials, 2022)
In this study, the apparent interlaminar shear strength (ILSS) of unidirectional (UD) viscose fibre-reinforced epoxy composites was characterised using different test methods. The transverse tensile test, short beam shear test, single edge notched bending test (SENB), double-notched tensile test and double-notched compression test were used. The composites were produced from continuous tows with fibre mass fractions of 20, 30 and 40% and fibres of different fineness (1.7, 3.3 and 28.0 dtex). The results showed that the different test procedures led to different trends of ILSS depending on the fibre mass fraction and fibre diameter used. The transverse tensile test revealed that the ILSS decreased with increasing fibre mass fraction and fibre diameter. A different trend was found with the short beam shear test and the SENB test. Here, higher values were detected with increasing fibre mass content, and the influence of the fineness was less noticeable. The double-notched shear tests (tensile and compression) showed a another trend: the ILSS increased with increasing fibre mass fraction from 20 to 30%. With a further increase to 40%, the ILSS tend to decrease slightly. An influence of the fibre fineness on the ILSS could not be statistically proven. The different trends of the test methods are attributed to the constitution of the composite and the different load application caused by the test procedures.